Characteristics of Submacular Hemorrhages in Age-Related Macular Degeneration. Issue 5 (May 2017) - Kim, Jae Hui; Chang, Young Suk; Kim, Jong Woo; Kim, Chul Gu
ABSTRACT: Purpose: The aims of this research are to report the incidence and characteristics of submacular hemorrhage secondary to neovascular age-related macular degeneration (AMD) and to compare the detailed morphologic features of hemorrhages between typical neovascular AMD and polypoidal choroidal vasculopathy (PCV). Methods: This retrospective observational study included 791 eyes of 791 patients who had newly diagnosed neovascular AMD at a single institution. The incidence and extent of submacular hemorrhage of one disc area or greater were estimated and compared between typical neovascular AMD and PCV. In addition, submacular hemorrhages were classified into groups according to location (location of fovea at the center of the hemorrhage versus at the periphery of the hemorrhage) and morphology (circular versus irregular margin). The proportion of each subtype of neovascular AMD was evaluated according to the aforementioned classification. Results: Among those included, 129 (16.3%) eyes exhibited submacular hemorrhage at initial presentation. Among the 627 eyes with available indocyanine green angiography findings, the incidence of submacular hemorrhage was greater in PCV (23.6%, 78 of 330 eyes) than in typical neovascular AMD (9.4%, 28 of 297 eyes; χ 2 test, P < .001). When divided into four groups according to hemorrhage shape and location (central and circular, central and irregular, peripheral and circular, and peripheral irregular), the proportion of eyes in these groups was significantly different between the two disease groups (χ 2 test, P = .018). Conclusions: The incidence of submacular hemorrhage was greater in PCV than in typical neovascular AMD. The morphology and location of submacular hemorrhage may provide useful clues to differentiate PCV from typical neovascular AMD.